Analisis Psikis Pekerja Di Masa Pandemi: Apakah Konflik Kerja, Beban Kerja Serta Iklim Organisasi Sebagai Antesenden Dari Stress Pekerja? - Pardongan Sihombing; Dian Marlina Verawati; Ivo Novitaningtyas (Universitas Nusa Putra, 2023)
The company's environment often experiences changes both internally and externally. The purpose of this study is to find out how psychologically workers are during a pandemic by knowing how the influence of work conflict, workload and organizational climate on worker stress during a pandemic. The approach used in this study is a quantitative approach with multiple linear regression analysis. The results of research conducted at Trio Plaza Magelang with a sample of 93 people found that the work conflict variable had a significant positive effect on work stress. The results of the multiple regression test obtained that the value of 0.261 is positive, indicating that the direction of the influence of work conflict on the level of work stress is positive. The sig value of 0.04 less than 0.05 indicates that there is a significant effect between work conflict and work stress. The regression results for the workload variable show that the workload has a positive but not significant effect. This is evidenced by the workload coefficient value of 0.304 indicating the direction of the influence of workload on work stress levels in a positive direction. A significant value of 0.156 indicates that there is no significant effect between workload and work stress. The regression results for the organizational climate variable show that organizational climate has an insignificant negative effect. The coefficient value obtained is -0.193, indicating that the organizational climate towards work stress has a negative direction. The significant value found is 0.332, indicating that the value is greater than 0.05, which means that the organizational climate on work stress is not significant.